INTERNALIZATION OF THE VALUE OF MUTUAL TRUST IN IMAM MUSLIM HADITH AS THE BASIS FOR RELIGIOUS CHARACTER FORMATION IN ISLAMIC EDUCATIONAL INSTITUTIONS - Khoir, Qoidul; Abror Rosyidin, Muhammad; Damanhuri (International Journal of Multidisciplinary Reseach, 2025)
This research aims to analyze the meaning and implementation of the value of mutual trust in Imam Muslim Hadith No. 1551 as the basis for forming religious character in Islamic educational institutions. This hadith contains moral principles about Islamic brotherhood, social responsibility, and empathy that are relevant to efforts to build trust between individuals in the world of education. The novelty of this research lies in its approach, which integrates the study of hadith texts with the practical realities of education, resulting in a model for internalizing religious values that is applicable and contextual in the modern era. This research uses a qualitative approach with field research combined with content analysis of hadith texts. Data collection techniques were carried out thru observation, in-depth interviews with teachers and pesantren caregivers, and documentation of learning activities in Islamic educational institutions. The research results indicate that the internalization of mutual trust values is implemented thru integration into the learning curriculum, teacher role modeling, and the formation of an institutional culture based on honesty, responsibility, and social solidarity. This process has a positive impact on improving students' spirituality, morality, and social care. Thus, the value of mutual trust in Imam Muslim Hadith No. 1551 can be used as a conceptual foundation and practical model for strengthening religious character education in Islamic educational institutions.